Pengaruh Persepsi Kemudahan Penggunaan dan E-Trust terhadap Keputusan Berdonasi Digital Generasi Z pada Aplikasi Kitabisa - Kamal Taufiqurohman; Arif Fadilla (Da'watuna: Journal of Communication and Islamic Broadcasting, 2022)
This study itself aims to understand whether the practice of perceived ease of use and e-trust built by the Kitabisa application has a significant influence on the realization of digital donation decisions in Generation Z in Indonesia. This study uses quantitative research methods in the process focusing on empirical data collected with a research approach because it uses descriptive and verification methods. The sampling technique used in this study is a purposive sampling technique using a google form in the process of collecting the required data. The data analysis technique used is path analysis technique with the help of Microsoft Excel and SPSS. The results of the hypothesis both from the simultaneous test or test that the perception of use and e-trust have a positive and significant effect on the decision to donate digital with a simultaneous effect of 64.5% and 35.5% are influenced by things that are not examined. Keywords: Digital Donations, Perceived Ease Of Use, E-Trust, Kitabisa